2010
DOI: 10.1186/1471-2458-10-774
|View full text |Cite
|
Sign up to set email alerts
|

Contingency management to reduce methamphetamine use and sexual risk among men who have sex with men: a randomized controlled trial

Abstract: BackgroundMethamphetamine use is associated with HIV acquisition and transmission among men who have sex with men (MSM). Contingency management (CM), providing positive reinforcement for drug abstinence and withholding reinforcement when abstinence is not demonstrated, may facilitate reduced methamphetamine use and sexual risk. We compared CM as a stand-alone intervention to a minimal intervention control to assess the feasibility of conducting a larger, more definitive trial of CM; to define the frequency of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 41 publications
1
43
0
Order By: Relevance
“…Second, frequency of assessment and size of reinforcement in CM-Lite were substantially reduced from typical levels. Notably, our study is consistent with findings from another recent trial (Menza et al, 2010) that found no effects for a CM intervention with a mean received total incentive level of $112 (compared with the mean of $461 in Heil et al, 2008). Third, we intentionally did not pair CM-Lite testing sessions with encouragement or advice and did not utilize shaping by ensuring that participants could obtain an initial success.…”
Section: Discussionsupporting
confidence: 87%
“…Second, frequency of assessment and size of reinforcement in CM-Lite were substantially reduced from typical levels. Notably, our study is consistent with findings from another recent trial (Menza et al, 2010) that found no effects for a CM intervention with a mean received total incentive level of $112 (compared with the mean of $461 in Heil et al, 2008). Third, we intentionally did not pair CM-Lite testing sessions with encouragement or advice and did not utilize shaping by ensuring that participants could obtain an initial success.…”
Section: Discussionsupporting
confidence: 87%
“…Contingency management (CM) interventions have also been used to treat crystal meth abuse [63][64][65][66][67][68][69] ; however, there is conflicting evidence regarding CM's efficacy. CM is a psychotherapy that provides rewards (e.g., cash or vouchers exchangeable for goods) for the achievement of specific treatment goals (e.g., abstinence from drug use or treatment session attendance).…”
mentioning
confidence: 99%
“…The reasons for each decision are given in Appendix 3. Articles were excluded for not being a RCT or other suitable study, as specified in our inclusion criteria; not having the sufficient percentage of MSM in the study population; [137][138][139][140][141][142][143][144][145] not including a sufficient percentage of HIV-negative participants; [146][147][148][149][150][151][152][153][154][155][156] or not being an individually focused intervention, instead focusing on groups or structural factors. [157][158][159][160][161][162][163][164][165][166][167] Other reasons for exclusion, such as interventions not being brief, reporting a pilot trial, reporting non-HIV-specific data (e.g.…”
Section: -106mentioning
confidence: 99%